Dietary Inclusion Levels Of Ensiled Avocado (Persia Americana) Oil Cake Into Pig Diets And Their Effects On The Growth Performance, Nutrient Digestibility, Carcass Characteristics And Meat Quality - Seshoka, Mmaseala, Lynette. (Central University of Technology, Free State, 2019)
The value of ensiled avocado (Persia Americana) oil cake (AOC) in pig diets was evaluated through three experiments. The first experiment was conducted to evaluate the effects of an enzyme addition on the fermentation characteristics, nutritive value and aerobic stability of ensiled AOC. An amount of 700 g AOC /kg fresh matter (FM) was mixed with 250 g wheat bran/kg FM, and 50 g sugarcane molasses/kg FM. This mixture was treated without i) additive (control), or with enzyme (Axtra® XB enzyme) at ii) 3 % and iii) 5% levels, making three treatments in total. The enzyme contained endo-1, 4-β-xylanase (12.200 U/g) and endo 1,3β-gluconase, (1.520 U/g). The forage mixtures were thoroughly mixed and compacted into 1.5 L anaerobic jars. Jars were kept at 25-28◦C room temperature for 90 days and there were 36 jars with nine jars per treatment. Samples of the pre-ensiled mixtures were collected for the determination of nutritive values, pH and water soluble carbohydrates (WSC). Three jars per treatment were then opened on days 3, 7, 10 and 90 post ensiling to determine pH while those of day 90 were also used to determine nutritive values and fermentation profiles of the treatments. Further, silage samples of day 90 were subjected to an aerobic stability test that lasted for 7 days. It was found that good quality silage can be produced from AOC without (P >0.05) the addition of enzyme. However, the effect of enzyme addition was apparent (P<0.05) on the reduction of NDF and increased WSC of ensiled AOC compared to the untreated silage. Although enzyme addition was applied at two different levels (i.e. 3 and 5 %), increasing enzyme addition to AOC at ensiling was not worthwhile since it did not make any significant contribution. The second experiment was conducted to evaluate the effect of different dietary inclusion levels of AOC silage on the growth performance, nutrient digestibility and carcass characteristics in pigs. In this experiment, AOC silage was produced without enzyme additive and ensiled in 200 L drums for 90 days. Experimental diets that contained different levels of AOC silage (i.e. 0, 3 and 5%) were formulated and fed to twenty-seven Large White x Landrace (LW x LR) pig crosses, weighing approximately 22 kg live weight. The pigs were randomly allocated to the three experimental diets (9 pigs/ treatment) balanced on their live weights. Pigs were individually weighed at the start and weekly until the end of the trial. Data on daily feed intake, average daily gains and feed conversion rates were recorded. A nutrient digestibility study whereby daily feed intake and the outputs of faeces and urine were measured, was done a week after completion of the growth study. At the end of the nutrient digestibility experiment, pigs were fasted for twelve hours and weighed to determine the final weight. The pigs were then slaughtered at an abattoir and carcass samples were collected and analysed. The growth performance of pigs was not (P >0.05) affected by dietary inclusion levels of AOC silage, irrespective of increased fibre levels in the AOC silage diets. However, dietary addition of 3 % AOC silage improved (P<0.05) the digestibility of fibre fractions. The cold carcass weight and the chop were reduced (P<0.05) with AOC silage addition. In addition, AOC silage reduced (P<0.05) the back fat thickness of the pig carcasses, which has positive implications for human consumption. A third experiment was conducted to evaluate the effect of different dietary inclusion levels of enzyme on the growth performance, nutrient digestion and carcass characteristics in pigs. In this experiment, AOC silage was produced without enzyme additive and ensiled in 200 L drums for 90 days. A total mixed ration that contained 5 % AOC silage was formulated. The diet was top dressed with enzyme at 0, 2.5 and 5 % of the daily ration of pigs. Twenty-four Large White x Landrace (LW x LR) crosses, weighing approximately 22 kg live weight were used. The pigs were randomly allocated to the three experimental diets (8 pigs/ treatment) balanced on their live weights. Pigs were individually weighed at the start and weekly until end of the trial. The pigs were fed on experimental diets ad lib in the morning, allowing a 10 % of feed refusal, and free access to water was allowed. Data on daily feed intake, average daily gains and feed conversion rates were recorded. The dietary treatments were fed to growing pigs for 60 days. Growth performance, nutrient digestibility and carcass traits were evaluated. A nutrient digestibility study was done a week after completion of the growth study. Daily feed intake and the outputs of faeces and urine were measured. At the end of the nutrient digestibility experiment, pigs were fasted for twelve hours and weighed to determine the final weight. The pigs were then slaughtered at an abattoir and carcass samples were collected and analysed. This study showed that the addition of enzymes during the feeding of AOC silage diets to growing pigs improved (P <0.05) the dry matter intake (DMI) and nutrient digestibility without (P >0.05) improving average daily gains (ADG) and feed conversion rates (FCR) in pigs. Further, the carcass characteristics of pigs were not (P>0.05) affected by diets, but the small and large intestines were increased (P<0.05) with enzyme addition. The meat colour and the cooking quality were not (P>0.05) affected by dietary treatments. Increasing the enzyme addition to the pig diets was not worthwhile, and enzyme addition only affected the feed intake and nutrient digestion. It was concluded that the AOC can be ensiled and used at less than 5 % in the diets of growing pigs without any detrimental effects on the growth of pigs.
Keywords: Additives; Digestion; Fats; Feed; Fermentation